Simulation peculiarities of the navigation information measuring devise based on dynamically tuned gyro - Сущенко, О.А. (Proceedings of National Aviation University, 2005)
Simulation peculiarities of the navigation information measuring devise based on dynamically tuned gyro are analyzed. Possibilities of its use in different operating modes of the navigational systems are described. The device accuracy at the mode of the angle rate measurement is researched.